Analisis Penerapan Sistem Tapping Box Untuk Pajak Restoran (Studi Kasus Badan Pendapatan Daerah Kabupaten Manggarai Barat) - Vonisia Jelina; Ni Wayan Noviana Safitri (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
The purpose of this study was to determine the working system of the tapping box, the advantages and disadvantages of implementing the tapping box system and also to determine the obstacles faced by the Regional Revenue Agency of West Manggarai Regency in implementing the tapping box system policy. This study is a qualitative study. The population and sample in this study were staff of the Regional Revenue Agency of West Manggarai Regency. The sampling method used was purposive sampling. The data used in this study were primary and secondary data collected through interviews, observations, and documentation. The results of the study indicate that the implementation of this tapping box system has implications for achieving the target of restaurant tax revenue in 2016-2023 in West Manggarai Regency. The obstacles faced in implementing the tapping box system in West Manggarai Regency are that restaurant taxpayers do not understand the tapping box system, the available tools are still minimal, and taxpayers refuse to install the system because the price will increase and have an impact on visitors. Based on the research findings, the advice that can be given to the Regional Revenue Agency of West Manggarai Regency is the importance of conducting socialization and education about the importance of tapping boxes routinely and accurately.